Lumbosacral transitional vertebrae of 3096 individuals: Prevalence and morphology in a South African population and its association with population affinity - G.J. Paton; S.A. Williams; S. Nalla; G.J. Louw (Translational Research in Anatomy, 2024)
Purpose: This study sought to establish the prevalence and morphological characteristics of lumbosacral transitional vertebrae (LSTV) in the South African population and its correlation with South African's population affinities. Methods: A retrospective review was performed of 3096 consecutive thoracic-abdominal-pelvic radiographs at two large public hospitals in South Africa. Categorisation of LSTV was classified according to Castellvi et al. (1984): Types II, III, and IV with unilateral (A) or bilateral (B) subtypes present. The three largest South African population groups (participant self-identified), namely Black African, Coloured and White population affinities were equally sampled, comprising 1032 radiographs for each population affinity. Results: The overall prevalence of LSTV was 10 % (N = 308 of 3096). Prevalence by classification/type was 67.9 %, 27.6 % and 4.5 % for II, III, and IV, respectively. The most prevalent subtype was Type IIA (41.9 %), Type IIB (26 %), Type IIIB (21.8 %), and Type IV (5.8 %), respectively. Prevalence by frequency of side was bilateral (47.7 %), left (26.6 %), right (21.1 %), while 4.5 % could not be sided (Type IV morphology). The sex distribution was 53.9 % (166/308) female and 46.1 % (142/308) male. Prevalence by population affinity was 10.5 %, 9.3 % and 9.9 % for the Black African, Coloured and White population affinities, respectively. Analyses of all groups found that the Black African and Coloured populations demonstrated two statistically significant results: greater affinity for the prevalence of sacralisation (95 % CI: 0.396–4.33, p = 0.008), and sacralisation amongst males (95 %, CI: 0.42–3.36, p = 0.010). Conclusion: This study was the first dedicated study of LSTV prevalence in a South African population. There was no significant difference in the prevalence of LSTV between the three largest population groups. Statistically, sacralisation was observed in greater proportions in the Black African and Coloured populations, particularly among males.